2015
DOI: 10.3892/br.2015.560
|View full text |Cite
|
Sign up to set email alerts
|

Associations of platelet-activating factor acetylhydrolase gene polymorphisms with risk of ischemic stroke

Abstract: Abstract. Platelet-activating factor acetylhydrolase (PAF-AH) has an important function in the pathogenesis of ischemic stroke. The aim of the present study was to investigate the correlation between the variation of polymorphisms (R92H and V279F) in PAF-AH and ischemic stroke. A total of 375 patients with ischemic stroke and 370 healthy controls were recruited into the study. Polymorphisms of V279F and R92H in PAF-AH were detected by polymerase chain reaction and DNA direct sequencing method. No significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This resulted in an overall decrease of microglia in the brain as measured by flow cytometry (Aertker et al., 2019). In the absence of infiltrating macrophages, there is less activation of resident microglia (Ma, 2016). Further investigations to delineate between infiltrating macrophages and resident microglia after TBI are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in an overall decrease of microglia in the brain as measured by flow cytometry (Aertker et al., 2019). In the absence of infiltrating macrophages, there is less activation of resident microglia (Ma, 2016). Further investigations to delineate between infiltrating macrophages and resident microglia after TBI are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For vascular diseases, the effect of the R92H variant was inconsistent in different studies. Along the lines of the results summarized by Stafforini in the European population, the H92 variant was associated with an increased risk of vascular diseases in the Chinese population by Zheng et al (OR = 1.81, 95% CI: 1.18‐2.78), Xu et al (OR = 1.63, 95% CI: 1.02‐2.62), Ma (OR = 1.42, 95% CI: 1.02‐2.00), Hong et al (OR = 2.66, 95% CI: 1.50‐4.69), and Chi et al (OR = 1.45, 95% CI: 1.16‐1.92). Additionally, a recent meta‐analysis also yielded a significantly positive association between R92H mutation and clinical atherosclerosis (OR = 1.29, 95% CI: 1.09‐1.53) .…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 97%
“…Interestingly, inconsistent results were obtained even for the same ethnic population and disease as well. For example, a case‐control study demonstrated no significant association between the V279F mutation and ischemic stroke in a Chinese population (OR = 0.82, 95% CI: 0.44‐1.24), whereas another genetic study established an increased risk despite using the same study population and disease (OR = 2.51, 95% CI: 1.02‐5.91, P = .037) . In the case of atherosclerosis, a significant inverse association of V279F polymorphism with clinical atherosclerosis was indicated in a recent meta‐analysis (OR = 0.88, 95% CI: 0.81‐0.95, P = .0007), whereas another study did not reveal any significant associations between the V279F genotype and subclinical atherosclerosis using Mendelian randomization analyses .…”
Section: Genetic Variability and Regulation Of Expressionmentioning
confidence: 99%
“…[91][92][93] R92H mutation in PAF-AH enzyme is reported to contribute to ischemic stroke susceptibility in the eastern Chinese Han population studied. 94 Conclusions sPLA 2 s are among the smallest enzymes which perform various vital physiological functions. Despite their small size, sPLA 2 enzymes are complex puzzles with respect to their structure-function relationships.…”
Section: Spla 2 Mutations and Weight Loss In Patients With Chronic Obmentioning
confidence: 99%
“… 91 93 R92H mutation in PAF-AH enzyme is reported to contribute to ischemic stroke susceptibility in the eastern Chinese Han population studied. 94 …”
Section: Others Diseases Caused By Spla 2 Mutationmentioning
confidence: 99%